Normative Behavioral Thresholds for Short Tone-Bursts - Beattie, Randall C.; Rochverger, Ilanit (Journal of the American Academy of Audiology, 2001)
Although tone-bursts have been commonly used in auditory brainstem response (ABR) evaluations for many years, national standards describing normal calibration values have not been established. This study was designed to gather normative threshold data to establish a physical reference for tone-burst stimuli that can be reproduced across clinics and laboratories. More specifically, we obtained norms for 3-msec tone-bursts presented at two repetition rates (9.3/sec and 39/sec), two gating functions (Trapezoid and Blackman), and four frequencies (500, 1000, 2000, and 4000 Hz). Our results are specified using three physical references: dB peak sound pressure level, dB peak-to-peak equivalent sound pressure level, and dB SPL (fast meter response, rate = 50 stimuli/sec). These data are offered for consideration when calibrating ABR equipment. The 39/sec stimulus rate yielded tone-burst thresholds that were approximately 3 dB lower than the 9.3/sec rate. The improvement in threshold with increasing stimulus rate may reflect the ability of the auditory system to integrate energy that occurs within a time interval of 200 to 500 msec (temporal integration). The Trapezoid gating function yielded thresholds that averaged 1.4 dB lower than the Blackman function. Although these differences are small and of little clinical importance, the cumulative effects of several instrument and/or procedural variables may yield clinically important differences.Abbreviations: ANSI = American National Standards Institute, IHS = Intelligent Hearing Systems, peSPL = peak equivalent sound pressure level, ppeSPL = peak-to-peak equivalent sound pressure level, pSPL = peak sound pressure level
Keywords: Auditory brainstem response; behavioral tone-burst thresholds; Blackman gating function; repetition rate; Trapezoid gating function